Education Perspectives of Human Rights Based Approach to Development: Action Points for Duty Bearers and Rights’ Holders - Ige, Olumide Olakunle; Sebili, Olabisi Toyyibah (NIU Journal of Humanities; Vol 5 No 3 (2020): KIU Journal of Humanities, Vol. 5 No. 3, September 2020, 2020)
Although human rights based approach (HRBA) to development was adopted almost two decades ago by the signatory nations of the UN, it has become evident that many member nations are still struggling to accept the underlining concept of accountability, especially in the context of education. Whereas the approach is intended to be a fundamental policy change from the needs based approaches to a more methodological and analytical one capable of serving the development and learning needs of all children, the practice of education as far as cursory observations and research evidence can show, would suggest that human rights based approach is not within the immediate focus in the educational scheme of things in some nations. This paper discusses human rights based approach (HRBA) to development in educational perspectives with a view to highlighting the action points for its effective implementation in Nigeria. Drawing theoretical support from the Jean Jacques Rousseau’s Social Contract Theory and O'Dwyer and Unerman’s Downward Accountability Theory, it discusses HRBA from the development principles and perspectives to show the thread that connects education to development. It underlines the priority of HRBA in Education for All (EFA) and identifies some action points for effective implementation of the human rights based approach to education in Nigeria. The paper rounds off with a conclusion and some recommendations based on the points emanating from the paper. Keywords: Human Rights Based Approach, Rights Holders, Duty Holders, Accountability